2018
DOI: 10.1007/s00261-018-1598-9
|View full text |Cite
|
Sign up to set email alerts
|

3T multiparametric MR imaging, PIRADSv2-based detection of index prostate cancer lesions in the transition zone and the peripheral zone using whole mount histopathology as reference standard

Abstract: The diagnostic performance of PI-RADSv2 for clinically significant transition and peripheral zone prostate cancer was similar. However, there was a lower portion of PI-RADSv2 4 and 5 lesions in transition zone compared to peripheral zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 13 publications
1
16
1
Order By: Relevance
“…The results of some studies that compared mpMRI to whole-mount section analysis is shown in Table 2. While sensitivity differs substantially within the cohorts reported here (sensitivities ranging from 74.3% to 100%), an important finding is consistent in all of them, high sensitivity for csPC on a patient basis shows that mpMRI is a relatively reliable pretest before prostate biopsy [16,[27][28][29][30][31][32][33][34]. Equally important with the ongoing discussions on overdetection and overtreatment of PC is the limited sensitivity for low grade PC.…”
Section: The Pre-biopsy Settingsupporting
confidence: 77%
See 1 more Smart Citation
“…The results of some studies that compared mpMRI to whole-mount section analysis is shown in Table 2. While sensitivity differs substantially within the cohorts reported here (sensitivities ranging from 74.3% to 100%), an important finding is consistent in all of them, high sensitivity for csPC on a patient basis shows that mpMRI is a relatively reliable pretest before prostate biopsy [16,[27][28][29][30][31][32][33][34]. Equally important with the ongoing discussions on overdetection and overtreatment of PC is the limited sensitivity for low grade PC.…”
Section: The Pre-biopsy Settingsupporting
confidence: 77%
“…While this adoption is supported by the high detection rate of MRI-TB and SB, sensitivity on a lesion basis is not comparably high. In recent studies, detection rates on a lesion basis for any PC and csPC vary between 39% to 59% and 56% to 88%, respectively [ 16 27 28 29 30 31 32 33 34 ]. A summary of studies on this issue can be found in Table 2 .…”
Section: Main Bodymentioning
confidence: 99%
“…PI‐RADS category 3–5 lesions in the PZ had a higher csPCa rate (26.7% to 90.9%, respectively), which indicates that targeting should be considered high‐yield for PI‐RADS category ≥3 in the PZ, and low‐yield for PI‐RADS category 2 or 3 lesions in the TZ/CZ located in the middle or base of the prostate, which is in line with the previous studies. In the examination of whole prostate gland specimens, it was reported that approximately 30% of PCa was located in the TZ, and just 20% was located in the base of the prostate . PCa in the TZ was also of a lower cancer grade or lower pathological stage than that in the PZ .…”
Section: Discussionmentioning
confidence: 99%
“…However, a more effective way for clinicians to learn one disease is to learn a different yet similar disease analogically. The imaging manifestation of PTZC is similar to prostate peripheral zone cancer (PPZC) in some ways, and there are far more images of PPZC available [ 16 ]. Consequently, to deal with the scarcity of PTZC images and better differentiate them from BPH, we decided to imitate the human brain's analogical learning ability by combining TL and DCNN.…”
Section: Introductionmentioning
confidence: 99%